SO2 and BrO emissions of Masaya volcano from 2014 to 2020 - Dinger, Florian; Kleinbek, Timo; Dörner, Steffen; Bobrowski, Nicole; Platt, Ulrich; Wagner, Thomas; Ibarra, Martha; Espinoza, Eveling (Atmospheric chemistry and physics, 2021)
Abstract. Masaya (Nicaragua,12.0◦N,86.2◦W;635 m a.s.l.) is one of the few volcanoes hosting a lavalake, today. This study has two foci: (1) discussing thestate of the art of long-term SO2emission flux monitoringwith the example of Masaya and (2) the provision anddiscussion of a continuous data set on volcanic gas data witha large temporal coverage, which is a major extension of theempirical database for studies in volcanology as well as at-mospheric bromine chemistry. We present time series of SO2emission fluxes and BrO/SO2molar ratios in the gas plumeof Masaya from March 2014 to March 2020 – coveringthe three time periods (1) before the lava lake appearance,(2) a period of high lava lake activity (November 2015 toMay 2018), and (3) after the period of high lava lake activity.For these three time periods, we report average SO2emissionfluxes of (1000±200), (1000±300), and (700±200) t d−1and average BrO/SO2molar ratios of(2.9±1.5)×10−5,(4.8±1.9)×10−5, and(5.5±2.6)×10−5.Our SO2emission flux retrieval is based on a compre-hensive investigation of various aspects of spectroscopic re-trievals, the wind conditions, and the plume height. We observed a correlation between the SO2emission fluxes andthe wind speed in the raw data. We present a partial correction of this artefact by applying dynamic estimates for theplume height as a function of the wind speed. Our retrievedSO2emission fluxes are on average a factor of 1.4 larger thanformer estimates based on the same data.Further, we observed different patterns in the BrO/SO2time series: (1) an annual cyclicity with amplitudes between1.4 and 2.5×10−5and a weak semi-annual modulation, (2) astep increase by 0.7×10−5in late 2015, (3) a linear trend of1.4×10−5per year from November 2015 to March 2018, and (4) a linear trend of−0.8×10−5per year from June 2018 to March 2020. The step increase in 2015 coincided with thelava lake appearance and was thus most likely caused by achange in the magmatic system. We suggest that the cyclicity might be a manifestation of meteorological cycles. Wefound an anticorrelation between the BrO/SO2molar ratiosand the atmospheric water concentration (correlation coefficient of−0.47) but, in contrast to that, neither a correlationwith the ozone mixing ratio (+0.21) nor systematic dependencies between the BrO/SO2molar ratios and the atmospheric plume age for an age range of 2–20 min after the release from the volcanic edifice. The two latter observationsindicate an early stop of the autocatalytic transformation ofbromide Br−solved in aerosol particles to atmospheric BrO.
Im Titel ist "2" in SO2 tiefgestellt
Gesehen am 04.08.2021